Penggunaan Diksi Khususnya Pronomina Persona dalam Kegiatan Berbicara Siswa MAN 2 Kota Makassar - Tuti Wijayanti (Departement of Mathematics Education, 2023)
This study discusses the use of diction, especially our first plural personal pronouns in the speaking activities of students of MAN 2 Makassar City. The purpose of this study is to describe and interpret the use of diction, especially the first plural personal pronouns for students of MAN 2 Makassar City in speaking activities seen from social factors. This type of research is ex-post facto research. Based on the problems discussed, the type of data collected in this research is qualitative data. The results of the research show that in constructing sentences, our first plural plural personal pronouns are used very high. In each student's utterances, the word kita appears frequently. Only in relation to ethnicity, the plural personal pronoun we dominates in Bugis and Makassarese ethnicity with different meanings.